The twelve days of Christmas cats - Daily, Don (Kennebunkport, Maine : Applesauce Press, 2014)
Offers a version of the Christmas classic in which the gifts are a series of felines, from a kitten in a fir tree to twelve dapper dancers--six black cats in top hats and six white cats with red bows.
Keywords: Children's songs -- United States -- Juvenile literature; Christmas music -- Juvenile literature; Cats -- Songs and music; Carols; Christmas music; Songs